The Importance of Immediate Constructive Feedback on Students’ Instrumental Motivation in Speaking in English - Howes Sallang; Ying-Leh Ling (Britain International for Academic Research (BIAR) Publisher, 2019)
The research discusses the importance of immediate constructive feedback in increasing instrumental motivation towards English speaking. This is research is on the students’ perspectives as teachers advice on the students’ state of performance contributes to the students’ increased motivation in speaking the English language in a teaching and learning process. Therefore, this research provides the understanding that teachers’ behavior could compliment students’ increased instrumental motivation in learning English language during the teaching and learning process in their respective classroom would complement their proficiency in speaking in English language. 227 final year bachelor degree students of a private higher learning institutions from five schools; School of Business and Management, School of Engineering Technology, School of Built Environment and School of Computing and Creative Media are the samples of this research. The research instrument used in this research is a set of five Likert scale questionnaire and it brings a result of a relationship between immediate constructive feedback with students’ instrumental motivation and also that there is an influence of immediacy constructive feedback towards students’ instrumental motivation in speaking English language. Therefore, the research concluded that providing immediate constructive feedback is crucial in a teaching and learning process especially as it boosts students’ motivation in speaking in English language.